2010
DOI: 10.1002/imhj.20250
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic play in young children exposed to terrorism: An empirical study

Abstract: The phenomenon of "posttraumatic play" (PTP) has received much clinical recognition and little empirical support. The objective of this study was to examine various aspects of PTP in young children exposed to terror events and their relation to posttraumatic stress disorder (PTSD). Individual play sessions, conducted with 29 young Israeli children directly exposed to terrorism (M age = 5.47, SD = 1.34) and 25 matched unexposed children (M age = 5.62, SD = 0.87), were coded using the Children's Play Therapy Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 33 publications
0
21
0
7
Order By: Relevance
“…Such play is not just a ‘symptom’ of trauma, it also offers significant insight into the experience of traumatic events, and the meaning these hold in the child's life (Almqvist and Broberg, ). Cohen and others () completed play observations with a small sample of children who had experienced war‐related trauma, and compared this to their reported symptoms of PTSD. They found that children who engaged in mostly negative play, characterised by negative emotional expression and aggressive or morbid acting out, tended to have higher rates of post‐traumatic symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…Such play is not just a ‘symptom’ of trauma, it also offers significant insight into the experience of traumatic events, and the meaning these hold in the child's life (Almqvist and Broberg, ). Cohen and others () completed play observations with a small sample of children who had experienced war‐related trauma, and compared this to their reported symptoms of PTSD. They found that children who engaged in mostly negative play, characterised by negative emotional expression and aggressive or morbid acting out, tended to have higher rates of post‐traumatic symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…For example, they may experience increased depression, possibly for prolonged periods (Melhem, Porta, Shamseddeen, Payne, & Brent, 2011). In a school setting, young children may reenact death through play (Cohen, Chazan, Lerner, & Maimon, 2010) and experience strong emotions such as guilt and anger, often blaming themselves for being responsible for or not preventing the loss (Cohen, Mannarino, & Deblinger, 2006). Problems in four areas including physical (stomach aches and headaches), emotional (sadness and anxiety), cognitive (distraction or denial) and social (isolation and opposition) may be present (Heath et al, 2008).…”
Section: )mentioning
confidence: 99%
“…Gil a également nuancé des variations et des phases au concept du jeu posttraumatique, qui permettent de guider le clinicien dans le traitement des enfants traumatisés (le lecteur intéressé peut se référer à . Cohen, Chazan, Lerner et Maimon (2010) ont contribué également à l'élargissement clinique du concept du JPT depuis Terr. Pour eux, le JPT n'est pas juste le signe clinique d'une pathologie, mais d'adaptationrésilience (dans un effort pour maitriser le trauma).…”
Section: Le Jeu Post-traumatique : Expression Du Trauma Dans Les Jeuxunclassified
“…Leurs études ont visé à contribuer au fait que le JPT constitue une tentative adaptée de la part de l'enfant d'utiliser ses propres ressources pour faire face aux évènements traumatiques, et aussi un signal d'appel et de détresse signifiant que l'enfant a besoin d'aide. Pour Cohen et al (2010), de manière très caractéristique, le JPT plus toxique consiste en des thèmes répétitifs qui ne se résorbent pas (pas d'apaisement) et qui augmentent l'agressivité et/ou le retrait. Aussi, les fantaisies sont bien souvent reliées à la revanche ou au sauvetage, s'appuyant sur une symbolisation réduite et une pensée concrète.…”
Section: Le Jeu Post-traumatique : Expression Du Trauma Dans Les Jeuxunclassified
See 1 more Smart Citation